Reform On Integrated Public Service Management In The Regions Based On New Public Service - Cahyasari, Erlita (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The more developed a country is, the more complex the public service management it requires. Thus, increasing public service provision has been a huge challenge for big countries around the world, especially for a country like Indonesia that adopts decentralized system of governance. Hence, for Indonesia, it is important to formulate and reinforce the service standards (Minimal Service Standards, Public Service Standards, and Operational Procedures Standards). This writing emphasizes on the Standards that are meant to be the reference for around 590 regencies/cities across Indonesia in terms of the establishment of Public Service. Public service standards need to focus on the citizens’ basic needs and civil rights for goods, services, and administrational services. Basic public services, especially in education, health, and infrastructure sectors, are determinant or key factors for a better quality life in a society.